2016
DOI: 10.1080/15284336.2016.1177266
|View full text |Cite
|
Sign up to set email alerts
|

The Framingham function overestimates the risk of ischemic heart disease in HIV-infected patients from Barcelona

Abstract: The FRS significantly overestimates risk of IHE events in our HIV-infected patients, while the REGICOR function is a better predictor of these events. In terms of cardiovascular events, the REGICOR function significantly underestimates risk, whereas the FRS is a better estimator. We recommend using CVR scales and adjusting them to the origin of the population being studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In contrast, studies which have actually investigated the predictive performance of different algorithms have shown conflicting results 15,[17][18][19][20][21][22][23] . However, these studies were limited by the use of cross-sectional measurements of subclinical CVD endpoints (for which the algorithms were not designed) [24][25][26][27][28] , relatively small sample sizes resulting in a limited number of observed CVD events 17,21,23,25,[27][28][29] , a limited selection of algorithms for comparison [17][18][19][20][21]23,25,29 , and/or by not providing external validation 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies which have actually investigated the predictive performance of different algorithms have shown conflicting results 15,[17][18][19][20][21][22][23] . However, these studies were limited by the use of cross-sectional measurements of subclinical CVD endpoints (for which the algorithms were not designed) [24][25][26][27][28] , relatively small sample sizes resulting in a limited number of observed CVD events 17,21,23,25,[27][28][29] , a limited selection of algorithms for comparison [17][18][19][20][21]23,25,29 , and/or by not providing external validation 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…An update from D:A:D: study concluded that Framingham model performed well compared to DAD equation for global CVD risk [6]. In contrast a study from Spain showed that Framingham risk equation significantly overestimated ischemic heart events in South-European HIV-infected patients [7]. We assessed the agreement between predicted global CVD risk according to the Framingham equation [4] and observed CVD morbidity in a consecutive series of HIV-positive subjects who were followed up until 10 years.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 , 17 , 18 , 19 Curiously, the Framingham risk score overestimated heart events in a Mediterranean HIV-infected population and a Regicor chart (an adaption for the characteristics of the Spanish population) worked better as a predictor for ischemic CV events. 20 Some intrinsic characteristics of this Spanish population may explain this different impact of Framingham score as it usually underestimates CV risk in HIV-infected populations. Only 26.1% of our patients were stratified as high-risk by Framingham compared to 46% by ACC/AHA.…”
Section: Discussionmentioning
confidence: 97%